IMAGE PROCESSING MOBILE APPLICATION FOR BANANA RIPENESS EVALUATION - MIRZA SYAZWANA, MOHAMAD NOOR (Universiti Malaysia Sarawak (UNIMAS), 2018)
The main objective of this project is to develop an expert system tool for evaluating the ripeness of banana fruit. Mobile application has been identified as the best platform for the expert system tool to reach as many users as possible. By utilizing Google Cloud Platform, the application will send the sample banana image through Google Vision API to get attributes readings from the image sample. The result of the analysis will be compared with application’s database of attributes datasets to determine the ripeness of the sample banana. The ripeness of banana is classified to unripe, ripe and overripe systematically based on their key attributes value. This project will also involve the process of collecting samples of banana with different level of ripeness, application development and evaluation to improve the accuracy of the develop applications classification results using image processing and data mining techniques. The significance of this project is being able to aid those who suffered colour blindness and local small farmers. The novelty of this project is the implementation of banana ripeness classification into a multi-platform mobile application.